2021
DOI: 10.5423/ppj.oa.10.2020.0193
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Structure of Blumeria graminis f. sp. avenae Populations in Poland across 2014-2015

Abstract: The purpose of this study was to determine the virulence structure of oat powdery mildew ( Blumeria graminis f. sp. avenae , Bga ) populations in Poland collected in 2014 and 2015. Powdery mildew isolates were collected from 18 locations in Poland. In total, nine lines and cultivars of oat, with different mildew resistance genes, were used to assess virulence of 180 isolates. The results showed that a significant proportion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Due to the lack of a line with a single Pm8 gene, this cultivar was included in the control set. Numerous of our own observations show that the Pm8 gene does not show a high level of resistance [33].…”
Section: New Nomenclature For B Graminis Fsp Avenae Phenotypesmentioning
confidence: 79%
See 2 more Smart Citations
“…Due to the lack of a line with a single Pm8 gene, this cultivar was included in the control set. Numerous of our own observations show that the Pm8 gene does not show a high level of resistance [33].…”
Section: New Nomenclature For B Graminis Fsp Avenae Phenotypesmentioning
confidence: 79%
“…This number is growing successively from year to year. The number of pathotypes was two in 2010 and increased to eight in 2015 [33,38]. In recent years, this has ranged from 12 in 2016 to 21 in 2019.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure and dynamics of changes in pathogen populations can be analysed using two different approaches. The first is based on the assessment of the virulence level of the pathogen population [ 19 , 21 , 22 , 23 , 24 , 25 , 26 ]. This approach allows us to determine the effectiveness of resistance genes used in breeding and to estimate the possibility of breaking this resistance by emerging pathogen races.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the virulence of oat powdery mildew have already been reported several times in the literature [ 18 , 19 , 20 ]. However, there is no information on research into the genetic diversity of B. graminis f. sp.…”
Section: Introductionmentioning
confidence: 99%